1997
DOI: 10.1007/s004030050194
|View full text |Cite
|
Sign up to set email alerts
|

Binding and in vitro modulation of human epidermal Langerhans cell functions by substance P

Abstract: Substance P (SP) is distributed in both the central and peripheral nervous system. It has various effects on immunocompetent cells, such as macrophages and lymphocytes. The aim of our study was to search for the presence of SP receptors (SP-R) on human cutaneous Langerhans cells (LC), and to determine the effects of SP on LC immunological functions in a model of mixed epidermal cell-lymphocyte reaction (MELR). Radioligand binding studies showed that LC-enriched epidermal cell suspensions reversibly bound SP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Importantly, our data demonstrate for the first time constitutive expression of the NK1R by murine LCs, indicating that signaling LCs directly via the NK1R may affect their APC function and ability to express transgenes. Accordingly, neuropeptides such as SP and calcitonin gene-related peptide, secreted by cutaneous ␦ fibers, exert important immune-modulation of LCs (13) and previous reports (23,64) have shown that the NK1R agonist down-regulates the migratory function of LCs. However, our results clearly indicate that the NK1R agonist triggers a massive and rapid LC mobilization of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our data demonstrate for the first time constitutive expression of the NK1R by murine LCs, indicating that signaling LCs directly via the NK1R may affect their APC function and ability to express transgenes. Accordingly, neuropeptides such as SP and calcitonin gene-related peptide, secreted by cutaneous ␦ fibers, exert important immune-modulation of LCs (13) and previous reports (23,64) have shown that the NK1R agonist down-regulates the migratory function of LCs. However, our results clearly indicate that the NK1R agonist triggers a massive and rapid LC mobilization of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…12 No entanto, deve-se mencionar que isso é uma generalização e que há resultados de efeitos inibitórios da SP em altas concentrações sobre a resposta de células T em modelos de HTT in vitro que podem ser de alguma relevância in vivo. 132 O CGRP, por sua vez, tem sido intensamente estudado em sua capacidade de inibir as reações de HTT por suprimir a apresentação de antígeno por células de Langerhans (vide acima, na descrição do peptídeo). Na pele, há fibras imunorreativas para o CGRP em íntimo contato com células de Langerhans.…”
Section: Reações De Hipersensibilidadeunclassified
“…This action most often happens via receptors coupled with protein G. Neuromediators modulate functions of all cutaneous cell types: endothelial cells, muscle cells, eccrine or apocrine glandular cells, immune cells, fibroblasts, epidermal cells. In a mixed lympho-epidermal reaction in humans, substance P [93] can inhibit antigen presentation to lymphocytes, though NK1-type receptors on both Langerhans cells and T lymphocytes. In a similar model on mice, CGRP inhibits the presentation of antigens [43].…”
Section: Functional Connectionsmentioning
confidence: 99%
“…Langerhans cells produce pro-opiomelanocortin (precursor to MSH, ACTH and β-endorphin) [13]. Through receptors on their surface, the function of Langerhans cells is modulated by neuromediators: CGRP [43], substance P [93], GRP [94], and αMSH [87]. In atopic dermatitis, Langerhans cells seem to express the receptor for neuropeptide Y [76].…”
Section: Langerhans Cellsmentioning
confidence: 99%
See 1 more Smart Citation